Smart One-Channel Sensor Node for Ambient Vibration Test with Applications to Structural Health Monitoring of Large Civil Infrastructures. (17th November 2015) - Park, Young-Soo; Kim, Sehoon; Sim, Sung-Han; Koo, Ki-Young; Lee, Wontae; Lee, Jong-Jae
Abstract : Dynamic characteristics of structures have been monitored for safe operation and efficient maintenance of large civil infrastructures. For vibration data measurement, the conventional system uses cables, which cause very expensive costs and inconvenient installation. Therefore, various wireless sensor nodes have been developed to replace the conventional wired system. However, there still remain lots of issues to be resolved such as time synchronization between sensor nodes, data loss, data security, and power supply. In this study, Smart One-Channel Sensor Node (SOSN) was developed to measure vibration data, which can practically solve the issues on installation, time synchronization, and data storage. It is designed for temporal measurement with a limited capacity to operate for several hours using embedded batteries. Laboratory tests were carried out to verify the performance of the developed SOSN compared with conventional wired system. Its practical advantages were investigated through three full-scale tests on large civil infrastructures. Three field applications revealed that SOSN is a very practical tool for short-term monitoring of large civil infrastructures with respect to traffic control, installation time and convenience, secure data gathering, and so forth.